2021
DOI: 10.1111/ijcp.14266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propofol‐based total intravenous anaesthesia on postoperative cognitive function and sleep quality in elderly patients

Abstract: Colorectal surgery is a common surgical operation in clinic, and general anaesthesia is often used during the operation. As the surgery is a traumatic operation, the body will produce a series of stress reactions, leading to postoperative gastrointestinal adverse reactions such as abdominal pain and vomiting, which are not conducive to postoperative rehabilitation. Especially in elderly patients, with the increase of age, there are more basic diseases, coupled with the deterioration of the physiological functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Propofol dose, duration of surgery, and postoperative pain score also had potential effects on postoperative melatonin secretion in patients. [29][30][31] In our study, the propofol dose, and duration of surgery were balanced between the two groups, so the influence of the above-mentioned factors was negligible for our conclusions. Postoperative pain and circadian rhythm are bidirectionally affected.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol dose, duration of surgery, and postoperative pain score also had potential effects on postoperative melatonin secretion in patients. [29][30][31] In our study, the propofol dose, and duration of surgery were balanced between the two groups, so the influence of the above-mentioned factors was negligible for our conclusions. Postoperative pain and circadian rhythm are bidirectionally affected.…”
Section: Discussionmentioning
confidence: 99%
“…There is a relationship between propofol and POCD in clinical. Propofol is a short-acting intravenous anesthetic associated with the decreased risk of POCD and protecting patients from cognitive impairment injury [19,20]. Proinflammation cytokines and oxidative stress are the major cause of inflammation in cellular.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study by Ding et al [ 9 ] also indicated that propofol-based TIVA may effectively reduce the incidence of sleep disorders by inhibiting the release of cortisol and other inflammatory factors in addition to activating the secretion of melatonin. Although propofol anesthesia is not a real sleep state, some components of postoperative PSQI score might be affected by the residual effect of propofol after several half-lives of elimination that was supposed to be a very low plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is an ultra-short-acting intravenous anaesthesia drug for anaesthesia induction and maintenance that was commonly administered in total intravenous anesthesia (TIVA) with the advantages of rapid onset, easy control, and reasonable safety[ 7 , 8 ]. In addition, a previous study[ 9 ] observed that the propofol-based TIVA has limited effect on early postoperative sleep disorders assessed by the Pittsburgh Sleep Quality Index (PSQI)[ 10 ]. However, the utilization of propofol in treating insomnia or sleep disturbance remains controversial on account of previously reported accidental mortalities[ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%